Restorative Justice Paradigm as a Complement to Retributive Justice: A Review from the Perspective of Pancasila Philosophy - Azaris Pahlemy; Dwi Novantoro; Dominikus Rato; Fendi Setyawan (RADJA PUBLIKA, 2026)
This study employs a normative juridical approach. Following the enactment of the new Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) through Law Number 1 of 2023 concerning the Criminal Code and the new Indonesian Code of Criminal Procedure (Kitab Undang-Undang Hukum Acara Pidana/KUHAP) through Law Number 20 of 2025 concerning the Code of Criminal Procedure, both of which came into effect on 2 January 2026, there has been a paradigm shift in the focus of criminal punishment from a retributive justice approach to restorative justice. This paradigm shift arose because retributive justice has been unable to resolve the root causes of crime, has failed to provide adequate space for victim recovery, and has negatively affected social interactions within society. The restorative justice approach offers the concept that punishment should not merely be oriented toward retaliation, but should also take into account the rights and losses suffered by victims, while simultaneously seeking the restoration of social relations within the community. The paradigm of restorative justice is reflected in the minutes of the first session of the Investigating Committee for Preparatory Work for Indonesian Independence (Badan Penyelidik Usaha-Usaha Persiapan Kemerdekaan/BPUPK) held from 29 May to 1 June 1945, which became the embryo for the birth of Pancasila, stating that: “…so that in this era the State of Indonesia may be established, where people can live safely and prosperously, moving toward the attainment of perfect humanity. Therefore, the foremost legal requirement must be respect for human rights and obligations in the deepest sense.” Law enforcement cannot be separated from respect for humanitarian values, both from the perspective of perpetrators and victims, in order to realize a safe and prosperous society in accordance with the philosophy of Pancasila. Keywords: Law Enforcement, Concept of Justice, Pancasila Philosophy